Immunomodulators in Graves’ ophthalmopathy: a systematic review - Yeung, Antoinette; Siddiqui, Mohammed Saqlain; Mirtorabi, Neginsadat; Ahmed, Umnia Nasir; Watts, Emma; Sharma, Neil; Kumari, Reena; Boelaert, Kristien; Muzaffar, Jameel; Nieto, Hannah (Frontiers in Endocrinology, 2026)
BackgroundGraves’ Ophthalmopathy (GO), or thyroid eye disease, is an extrathyroidal complication of Graves’ disease, causing a significant impact on patients’ quality of life. There are consensus statements from both the American Thyroid Association (ATA) and the European Group on Graves’ Orbitopathy (EUGOGO) which provide guidance in management. However, there remain areas of ongoing debate and evolution in treatment approaches. This systematic review aims to evaluate immunomodulatory drugs in the treatment of GO.MethodsThe following databases were searched: Cochrane (CENTRAL), Embase, MEDLINE, ProQuest, PubMed, SCOPUS, and Web of Science. The last date of searching for each database was 10th October 2025. All primary studies on human patients with GO, treated with newer, targeted immunomodulatory therapies, in particular biologics and/or disease-modifying antirheumatic drugs, were included. Studies in languages other than English were excluded. The primary outcome of interest was Clinical Activity Score (CAS). A narrative synthesis was performed, including CAS and four other secondary outcomes. Cochrane risk of bias tools were used to assess quality of evidence. The study is registered on PROSPERO (CRD42023400285).ResultsOf 4839 records identified, 41 were eligible for data extraction. Teprotumumab and tocilizumab showed benefit in reducing CAS and proptosis, whilst rituximab was inconclusive. Methotrexate and reduced-dose steroids were beneficial in reducing CAS, and both methotrexate and cyclosporine with steroids were good for reducing proptosis. However, effects of immunomodulation on other secondary outcomes were unclear. Adverse events were higher in the steroid treated patients compared to all other drugs.ConclusionBiologics and steroid-sparing agents may be more effective than steroids at reducing CAS, but this is limited by the lack of head-to-head comparisons between drugs and significant heterogeneity amongst the included studies.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023400285.